Effect of the Harvest Year and Cultivation Temperature on the Germination of Hirschfeldia Incana (Brassicaceae): Inferences on Its Invasiveness in Chile - Castro-Morales, S (Springer International Publishing, 2016)
The hoary mustard (Hirschfeldia incana (L.) Lagr.-Foss.) is a recently alien weed in Chile, recording a rapid increase in local abundance and spread. This species is distributed mainly on urban ecosystems, and field observations suggest that seed germination may have a key role to understanding its population persistence. In this line, it has been suggested that a successful germination strategy for weeds is to have both persistent seeds in the soil as rapidly germinable seeds, extending the ability to germinate over time. We evaluated germination of seeds of H. incana according to different harvest years (2010, 2011, and 2012), searching to understand how harvest time affects seed germination. For this proposal, seeds were cultivated at different temperatures (eight levels between 5 and 40 °C), covering a wide thermal gradient. Our results showed a lower germination percentage (43 %) in seed harvested in 2012 compared to the harvested in 2010 and 2011 (both cases >60 %), supporting that Hirschfeldia delay seed germination but keeping a seed stock able to germinate the same year in which were produced. The maximum germination percentage (>80 %) occurred with temperatures between 20 and 35 °C, and germination did not occur at 5 °C. These results suggest that temperature is not limiting the geographical spread of H. incana in Chile, as temperatures <5 °C are unusual. Thus, we expect that H. incana may increase its local abundance and latitudinal spread, if appropriate measures are not taken in Chile. © 2015, Botanical Society of Sao Paulo.